Field Study of Deposit and Erosion Patterns around Pandanus Clusters on Sandy Coasts: a Preliminary Investigation - Nizam; Benazir; Ibrahim, Muhammad S. I.; Setyandito, Oki; Purnomo (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
Coastal zones are inherently dynamic, often resulting in long-term cumulative impacts such as erosion, which can potentially escalate into disasters. Discussions regarding nature-based solutions, particularly the utilization of coastal forests, have gained prominence due to their environ[1]mental benefits. This paper investigates the role of vegetated coasts in mitigating the effects of wave attacks on land, focusing specifically on Coastal Pandanus species. We conducted a systematic monitoring effort to quantify land changes directly around these species in the field. The southern coast of Java, characterized by significant coastal processes, served as the investigation site. We monitored the changes in the foredunes of eight Pandanus clusters identified along a 1 km stretch of the Pandansari and Samas coasts in the Special Region of Yogyakarta, Indonesia. Our systematic monitoring, conducted biweekly from September to December 2023, involved precise measurements of land elevation, sediment deposition, and erosion around the Pandanus clusters. We utilized manual leveling surveys and installed erosion pins to enhance the precision of our topographic assessments. These monitoring techniques allowed us to thoroughly examine the relationship between Pandanus cluster characteristics and coastal processes. Our findings illuminate the pivotal role of Pandanus clusters in shaping coastal profiles, which depend on cluster area and growth characteristics. Additionally, we underscore key points regarding their success rates, limitations, and future strengthening efforts through the implementation of this nature-based solution. This research contributes to a deeper understanding of the complex interactions between coastal dynamics and vegetative elements, paving the way for informed coastal management strategies in the future.